INSULIN RESISTANCE AND TYPE 2 DIABETES: A TRANSVERSAL ANALYSIS IN A NUTRITIONAL INTERVENTION PROGRAM - Rodrigues, Camila Neves; Cândido, Flávia Galvão; Alfenas, Rita de Cássia Gonçalves; Hermsdorff, Helen Hermana Miranda (Journal of Health Care, 2015)
Introduction: Insulin resistance (IR) is often associated with diabetes type 2 (DM2), that presents itself asa morbidity of important impact due to its possible complications. Objectives: To identify individuals IRand DM2 and to evaluate possible differences in their sociodemographic, anthropometrics, of body andclinical compositions, and feeding behavior characteristics. Materials and methods: This is an observationalcross-sectional study. The study included 68 patients enrolled in a nutritional intervention programfor the prevention and treatment of cardiovascular diseases. Data were collected from records concerningthe first query. To identify insulin-resistant individuals it was used the HOMA-IR>2,7. Results: Twentyseven individuals were classified as the control group, 21 as insulin resistant and non-diabetics and 20 asdiabetics. Both insulin resistant and diabetics had higher BMI (p=0,001), body fat (p=0,001), circumferenceof waist (p=0,001) and hip (p=0,002), compared to the control group. More hypertensive diabetics(70%) were observed. The insulin resistant had lower levels of HDL (p=0,009) and higher of uric acid(p=0,033) compared to controls and higher LDL (p=0,031) when compared to diabetic. Those reportedgreater use of animal lard (15,8%) and changing habits on weekends (84,2%). Conclusions: The results of this study emphasize the importance of early detection of IR and nutrition intervention programsaiming at the weight control and combat hypertension in diabetic as in insulin resistant.
Keywords: Diabetes mellitus; insulin resistance; feeding behavior; cardiovascular diseases.